2020
DOI: 10.1016/j.annonc.2020.08.1025
|View full text |Cite
|
Sign up to set email alerts
|

910O Primary results of the phase III JAVELIN head & neck 100 trial: Avelumab plus chemoradiotherapy (CRT) followed by avelumab maintenance vs CRT in patients with locally advanced squamous cell carcinoma of the head and neck (LA SCCHN)

Abstract: Background: p16 INK4a (p16) immunostaining is the most widely implemented technique in clinical settings for determining HPV causation and HPV-related prognosis biomarker of oropharyngeal cancer (OPC). A subset of p16+ OPC are HPV-; and their prognosis is still unclear. The aim of this study is to clearly define the proportion, determinants and prognosis of OPC patients who are p16+/HPV-. Methods:We established an international consortium comprising 13 cohorts of OPC patients with data on p16, HPV, demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 0 publications
0
20
0
2
Order By: Relevance
“…Similarly, afatinib therapy for 18 months after definitive CRT in patients with intermediate- to high-risk unresected HNSCC did not improve DFS [ 30 ]. The phase III JAVELIN head and neck 100 trial (NCT02952586) showed that stage III/IVA/IVB HNSCC patients using avelumab plus CRT followed by avelumab maintenance failed to show a statistically significant improvement in PFS compared with CRT alone [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, afatinib therapy for 18 months after definitive CRT in patients with intermediate- to high-risk unresected HNSCC did not improve DFS [ 30 ]. The phase III JAVELIN head and neck 100 trial (NCT02952586) showed that stage III/IVA/IVB HNSCC patients using avelumab plus CRT followed by avelumab maintenance failed to show a statistically significant improvement in PFS compared with CRT alone [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in locally advanced HNSCC using pembrolizumab or nivolumab with cisplatin and radiation were shown to be safe without unexpected toxicities [ 68 , 69 ]. However, the results of the Phase III JAVELIN Head and Neck 100 trial evaluating avelumab (PD-L1 inhibitor) plus CRT followed by avelumab maintenance versus CRT in patients with locally advanced HNSCC did not show any survival benefits (PFS stratified HR 1.21, 95% CI 0.93–1.57; stratified p -value 0.92 and OS stratified HR 1.31, 95% CI 0.93–1.85; stratified p -value 0.94; ClinicalTrials.gov Identifier: NCT02952586) [ 70 ]. The use of ICI as well as other targeted agents as maintenance therapy after CRT (ClinicalTrials.gov Identifier: NCT03811015 and NCT00079053) is under investigation.…”
Section: Management Of Newly Diagnosed Locally Advanced Hnsccmentioning
confidence: 99%
“…More recently, malignancies, in which ICIs have shown efficacy in metastatic setting such as head and neck cancer, were investigated in combination therapies consisting of ICI and RT. However, no added benefit was found after combined treatment compared to standard RT combined with chemotherapy or targeted drugs (cetuximab) in locally advanced setting, e.g., GORTEC 2015-01 “PembroRad” or JAVELIN Head and Neck 100 trials [ 174 , 175 ]. Another category, where the addition of ICI has not shown any added benefit, e.g., CheckMate 548 (NCT02667587), are stroma-rich but inherently immune-cold tumors, such as GBM and pancreatic cancer.…”
Section: Immunotherapeutic Options and Conventional Radiotherapymentioning
confidence: 99%